Partograph training: knowledge and attitude to implementation - Namangdjabar, Odi Lodia (Jurnal Kesehatan Ibu dan Anak, 2020)
One of the efforts to accelerate the reduction of MMR in the operation of antenatal services, by increasing the coverage of pregnant and childbirth services, one of which is the help of childbirth by using partographs. Partograph training aims to help birth attendants such as midwives can determine the attitude in the event of a long delivery so there is no delay in deciding to refer. This study aims to determine the effect of training treatment on midwives' knowledge and attitudes to implementation of partographs for women giving. The research in this study used Quasi Experiment Research. This research was conducted on a total sample of 48 midwives who worked in PHC in Kupang City that have Basic Emergency Neonatal Obstetric Services in 2019. Data analyzed using descriptive statistics and paired sample t-test. Most of the respondents are >30 years old (69.7%), have a Diploma in Midwifery education (75.8%), and have received partograph training (75.8%). There was a significant influence of partograph training to knowledge (Mean -35.625; 95% CI -38.674-(-32.576); p-value 0.000)and attitude (Mean -10.521; 95% CI -12.025-(-9.025); p-value 0.000). Partograph training has a great influence on the knowledge and attitudes of midwives in the implementation of partographs in childbirth mothers.